Implementasi Sistem Penilaian Kinerja Karyawan pada Kingbread - Adi Neka Fatyandri; Antonio Tantra Wijaya (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Kingbread, a bakery that has been operating since 2018, faces a major challenge in the form of employee indiscipline that has the potential to hinder the production and distribution process. To overcome this problem, Kingbread implemented an employee performance appraisal system that aims to improve productivity and discipline. The methods used include interviews, observations, documentation, and quantitative research to collect relevant data. The performance appraisal system is designed with key indicators such as responsibility, punctuality, quality of work, and communication, using a Google Form-based form for efficient data collection. The implementation results showed success in forming a comprehensive performance appraisal guide, creating an integrated data collection system, and producing in-depth performance analysis reports. Recommendations for further PkM include developing a training system based on individual employee needs, increasing the use of technology for data integration, and holding regular employee motivation programs. With this approach, Kingbread can continue to improve the quality of human resources, maintain productivity, and maintain competitiveness in the local market.